2022
DOI: 10.1183/23120541.00272-2022
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in interstitial lung disease: an area of unmet clinical need

Abstract: Pulmonary hypertension (PH) is present in an important proportion of patients with interstitial lung diseases (ILDs), encompassing a large, heterogeneous group of diffuse parenchymal lung diseases. Development of ILD-related PH is associated with reduced exercise capacity, increased need for supplemental oxygen, decreased quality of life and earlier death. Diagnosis of ILD-related PH is important and requires a high index of suspicion. Noninvasive diagnostic assessment can suggest the presence of PH, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Prevalence of PH in ILD varies widely in the studies, based on population studied and how PH was defined. The prevalence has been reported as high as 86%, however, this estimate varies between different types of ILD ( 6 ). The majority of prevalence data is derived from idiopathic pulmonary fibrosis (IPF), the most common ILD.…”
Section: Epidemiology: a Common Consortmentioning
confidence: 99%
“…Prevalence of PH in ILD varies widely in the studies, based on population studied and how PH was defined. The prevalence has been reported as high as 86%, however, this estimate varies between different types of ILD ( 6 ). The majority of prevalence data is derived from idiopathic pulmonary fibrosis (IPF), the most common ILD.…”
Section: Epidemiology: a Common Consortmentioning
confidence: 99%
“…Pulmonary hypertension secondary to ILD has been associated to reduced exercise capacity, increased need for supplemental oxygen, worse quality of life and prognosis ( 230 232 ). Screening for pulmonary hypertension should be performed in all RA-ILD patients although no recommendation on timing and frequency is available ( 233 ). Recently, the INCREASE trial ( 234 ) has shown significant improvements in exercise capacity in ILD patients with PH treated with inhaled treprostinil.…”
Section: The Current Clinical Practice In the Management Of Ra-ildmentioning
confidence: 99%
“…63 Regardless the initial inciting triggers, idiopathic pulmonary fibrosis (IPF) and some other fibrosing ILD are characterized by progressive fibrosis of the lung interstitium, sharing a common final pathway leading to an irreversible, and self-perpetuating profibrotic process. 64 65 The most extensive available data on PH associated with ILD refers to IPF. However, many other forms of ILD, including chronic hypersensitivity pneumonitis, connective tissue disease (CTD)-related ILD, sarcoidosis, and pulmonary Langerhans cell histiocytosis are also commonly associated with PH, although its prevalence varies greatly depending on the underlying disease.…”
Section: Pulmonary Hypertension In Interstitial Lung Diseasementioning
confidence: 99%
“…However, many other forms of ILD, including chronic hypersensitivity pneumonitis, connective tissue disease (CTD)-related ILD, sarcoidosis, and pulmonary Langerhans cell histiocytosis are also commonly associated with PH, although its prevalence varies greatly depending on the underlying disease. 65…”
Section: Pulmonary Hypertension In Interstitial Lung Diseasementioning
confidence: 99%